2017
DOI: 10.1007/978-1-4939-7371-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Hematopoietic Stem Cell Proliferation Using BrdU Incorporation

Abstract: Cellular quiescence is a key component of hematopoietic stem cell (HSC) homeostasis; therefore, a reliable method to measure HSC cell division is critical in many studies. However, measuring the proliferation rate of largely quiescent and rare populations of cells can be challenging. Bromo-deoxyuridine (BrdU) incorporation into replicating DNA is a commonly used and highly reproducible method to detect cell division history. Here, we describe a protocol for BrdU incorporation analysis in hematopoietic stem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Cell proliferation within the thyroid tumour tissue was investigated by IHC. Two markers were used; Ki67, a nuclear protein expressed during all active phases of the cell cycle (non-senescent cells) and BrdU which is incorporated during s-phase of the cell cycle [ 24 ]. This analysis demonstrated that proliferating cells were detectable in both freshly resected tissue and post-culture tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Cell proliferation within the thyroid tumour tissue was investigated by IHC. Two markers were used; Ki67, a nuclear protein expressed during all active phases of the cell cycle (non-senescent cells) and BrdU which is incorporated during s-phase of the cell cycle [ 24 ]. This analysis demonstrated that proliferating cells were detectable in both freshly resected tissue and post-culture tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Other markers include the DNA intercalating agents BrdU and EdU, which are absent or poorly retained in quiescent cells. However, both BrdU and EdU are unsuitable for downstream and lengthy analysis because they harm cells and induce mutations [ 81 ]. Fluorescent dyes are categorized according to their binding affinity to: (a) nucleic acids, (b) cytoplasm, (c) membrane, and d) cell cycle-related proteins.…”
Section: Measurement Of Quiescent Cancer Cellsmentioning
confidence: 99%
“…For analysis of the cell cycle, cells stained with antibodies to Ki-67 were briefly exposed to Hoechst 33342 before analysis. Analysis of BrdU incorporation in LSK cells was performed as previously described (Matatall et al, 2018).…”
Section: Lead Contactmentioning
confidence: 99%